2021
DOI: 10.1182/blood-2021-146798
|View full text |Cite
|
Sign up to set email alerts
|

Ixazomib Plus Lenalidomide/Dexamethasone (IRd) Versus Lenalidomide /Dexamethasone (Rd) Maintenance after Autologous Stem Cell Transplant in Patients with Newly Diagnosed Multiple Myeloma: Results of the Spanish GEM2014MAIN Trial

Abstract: Background: The Spanish Myeloma Group (GEM) demonstrated that post-transplant maintenance with thalidomide plus bortezomib was superior to thalidomide alone, although this combination was associated with a high rate of peripheral neuropathy. Lenalidomide is currently the standard postransplant maintenance treatment, and its association with ixazomib, an oral proteasome inhibitor that does not cause peripheral neuropathy, could be of interest. Aim: To assess the potential benefit of postransplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Several studies have assessed drug combinations as maintenance therapy after ASCT starting from lenalidomide, dexamethasone, and ixazomib (IRd) compared with Rd administered for two years in the GEM12MENOS65 trial. After a median follow-up of 56 months, adding ixazomib to Rd did not add benefit in terms of PFS [ 79 ]. On the contrary, carfilzomib combined with lenalidomide (KR) as maintenance resulted in improved PFS compared with lenalidomide (R) in the FORTE trial in which 3-year PFS was 75% vs. 65% in the KR and R group, respectively (HR = 0.64, p = 0.023) with no differences in terms of OS [ 19 ].…”
Section: Where We Are With Maintenance Therapymentioning
confidence: 99%
“…Several studies have assessed drug combinations as maintenance therapy after ASCT starting from lenalidomide, dexamethasone, and ixazomib (IRd) compared with Rd administered for two years in the GEM12MENOS65 trial. After a median follow-up of 56 months, adding ixazomib to Rd did not add benefit in terms of PFS [ 79 ]. On the contrary, carfilzomib combined with lenalidomide (KR) as maintenance resulted in improved PFS compared with lenalidomide (R) in the FORTE trial in which 3-year PFS was 75% vs. 65% in the KR and R group, respectively (HR = 0.64, p = 0.023) with no differences in terms of OS [ 19 ].…”
Section: Where We Are With Maintenance Therapymentioning
confidence: 99%
“…After a median follow-up of 56 months, the addition of ixazomib did not result in a progression-free survival benefit. 9 At the time the study was designed, continuous lenalidomide maintenance after ASCT did not demonstrate a benefit on overall survival and was not appoved. 10 In the present study, a fixed-duration maintenance with ixazomib alone appears to be a suboptimal approach for transplant-eligible NDMM patients.…”
mentioning
confidence: 99%
“…To date, ixazomib-based combinations have failed to significantly improve the outcome of transplant-eligible patients with NDMM. 8 , 9 This suboptimal efficacy can be partially explained by inferior in vitro proteasome inhibition with ixazomib in comparison with other proteasome inhibitors. 13 In NDMM patients, ixazomib could however be suitable for a specific subset of frail patients with comorbidities (e.g., pre-existing neuropathy, cardiac insufficiency), thought not to be able to tolerate bortezomib or carfilzomib-based combinations.…”
mentioning
confidence: 99%
“…Overall, ixazomib combined with Rd or as a single-agent maintenance therapy did not abrogate the negative impact of high-risk cytogenetic abnormalities, consistent with previously reported findings with ixazomib in non-transplant NDMM patients (TOURMALINE-MM2 [ 15 ]), the maintenance setting (TOURMALINE-MM3 [ 16 ] and TOURMALINE-MM4 [ 17 ]), and smaller real-world studies [ 20 , 21 ]. Additionally, in a recent study in NDMM patients, no significant improvement of PFS or OS was demonstrated with IRd maintenance vs Rd in patients with standard- or high-risk cytogenetics [ 22 ].…”
Section: Discussionmentioning
confidence: 99%